Anatomical-based percutaneous left stellate ganglion block in patients with drug-refractory electrical storm and structural heart disease: a single-centre case series. Issue 4 (15th November 2020) - Savastano, Simone; Dusi, Veronica; Baldi, Enrico; Rordorf, Roberto; Sanzo, Antonio; Camporotondo, Rita; Fracchia, Rosa; Compagnoni, Sara; Frigerio, Laura; Oltrona Visconti, Luigi; De Ferrari, Gaetano Maria
Abstract: Aims: The adoption of percutaneous stellate ganglion blockade for the treatment of drug-refractory electrical storm (ES) has been increasingly reported; however, the time of onset of the anti-arrhythmic effects, the safety of a purely anatomical approach in conscious patients and the additional benefit of repeated procedures remain unclear. Methods and results: This study included consecutive patients undergoing percutaneous left stellate ganglion blockade (PLSGB) in our centre for drug-refractory ES. Lidocaine, bupivacaine, or a combination of both were injected in the vicinity of the left stellate ganglion. Overall, 18 PLSGBs were performed in 11 patients (age 69 ± 13 years; 63.6% men, left ventricular ejection fraction 31.6 ± 16%). Seven patients received only one PLSGB; three underwent two procedures and one required three PLSGB and two continuous infusions to control ventricular arrhythmias (VAs). All PLSGBs were performed with an anatomical approach; lidocaine, alone, or in combination was used in 77.7% of the procedures. The median burden of VAs 1 h after each block was zero compared with five in the hour before ( P < 0.001); 83% of the patients were free from VAs; the efficacy at 24 h increased with repeated blocks. The anti-arrhythmic efficacy of PLSGB was not related to anisocoria. No procedure-related complications were reported. Conclusion: Anatomical-based PLSGB is a safe and rapidly effective treatment for refractory ES; repeated blocks provide additional benefits. Percutaneous left stellate ganglion blockade should be considered for stabilizing patients to allow further ES management.